2012
DOI: 10.1007/s10853-012-6855-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, electrical and electro-mechanical properties of thermoplastic elastomer styrene–butadiene–styrene/multiwall carbon nanotubes composites

Abstract: In this work composites of styrene-butadiene-styrene (SBS) block copolymer with multiwall carbon nanotubes (MWCNT) were processed by solution casting and their mechanical, electrical and electro-mechanical (gauge factor) response were characterised. Also investigated was the influence of the filler content in the polymer matrix, the different ratio of styrene/butadiene in the copolymer, and the architecture of the SBS matrix (radial, linear) on the electrical, mechanical and electro-mechanical properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…The Young modulus increases with decreasing butadiene in SBS and electrical percolation threshold is similar for the different SBS matrix [14].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The Young modulus increases with decreasing butadiene in SBS and electrical percolation threshold is similar for the different SBS matrix [14].…”
Section: Introductionmentioning
confidence: 82%
“…From equation (3) it is possible to observe that the GF has a contribution from the intrinsic piezoresistive effect ( In uniaxial stretching mode experiments (method 1) equation 2 was used for the calculation of the GF, using the evolution of the resistance during the stress-strain measurements. In 4-pointbending mode experiments (method 2), the mechanical strain was calculated from the theory of a pure bending plate to a cylindrical surface, valid between the inner loading points, and given by [14]:…”
Section: Electro-mechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they are used in many different fields, and not least, in the biomedical field [9]. Novel systems have been recently developed adopting polymers instead of the more conventional strain gauges, leading to sensors based on conductive polymers [10], polymer composites [11], polymer elastomers [12], thermoplastics [12], epoxies [13]. As a benefit, sensors based on polymers allow the use of conventional and convenient polymer processing and postprocessing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that polymer chain alignment during strain hardening is strongly affected by dispersing fillers within the host polymer matrix (8)(9)(10). To account for these observations, one needs to establish the relation between the macroscopically observed strain hardening and the microscopic chain alignment that is affected by the presence of fillers.…”
mentioning
confidence: 99%